The Commercial Philosophy of Suvarnabhumi on the Foundation of Buddhism - Chimwong, Sukanya (BUDDHO, 2022)
The commercial philosophy of Suvarnabhumi reflects the economic and trade principles of ancient Southeast Asia, which were significantly influenced by Buddhism. This article explores the Buddhist foundations that shaped the economic thought and practices in Suvarnabhumi, analyzing key Buddhist doctrines such as Right Livelihood (Sammā-ājīva), generosity (Dāna), and ethical conduct (Sīla). The study reveals that Buddhism is not merely a path to spiritual liberation but also plays a crucial role in shaping ethical and fair economic practices. The commercial system in Suvarnabhumi was deeply rooted in moral values, promoting sustainable and balanced trade. This research aims to demonstrate that the commercial philosophy of Suvarnabhumi provides valuable insights for establishing a more sustainable and equitable economic system in the modern world.